2014
DOI: 10.1016/j.jmbbm.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of the posterior human sclera

Abstract: To characterize the material properties of posterior and peripapillary sclera from human donors, and to investigate the macro- and micro-scale strains as potential control mechanisms governing mechanical homeostasis. Posterior scleral shells from 9 human donors aged 57–90 years were subjected to IOP elevations from 5 to 45 mmHg and the resulting full-field displacements were recorded using laser speckle interferometry. Eye-specific finite element models were generated based on experimentally measured scleral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 57 publications
4
119
0
Order By: Relevance
“…In engineering models, the behavior of both the peripapillary sclera and the lamina cribrosa determine the effect of IOP. [16][17][18] …”
mentioning
confidence: 99%
“…In engineering models, the behavior of both the peripapillary sclera and the lamina cribrosa determine the effect of IOP. [16][17][18] …”
mentioning
confidence: 99%
“…For example, scleral biomechanical properties may be altered by the initial IOP spike. 34,35 This effect may make the eye more vulnerable following insult. Further investigation is required to understand the role of the IOP spike in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that chronical IOP elevation induces significant structural changes in a thin porous tissue at the base of the optic nerve head called lamina cribrosa [2][3][4][5][6]. Elevated IOP may lead to vision loss by inducing mechanical damage on the retinal ganglion cells axons passing through the lamina (mechanical hypothesis) [7,8] and/or by altering the blood flow within the lamina's tissue (hemodynamical hypothesis) [9,10].…”
Section: Introductionmentioning
confidence: 99%